BUDAYA POLITIK MASYARAKAT LOKAL: STUDI KASUS DI KECAMATAN BANYUMANIK KOTA SEMARANG PASCA ORDE BARU - Arif Sofianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
There were many changes of national politics at the procedural level after the 1998 reform that affect the community's political orientation and activities. The purpose of this study was to understand changes in national politics at the procedural level after the 1998 reform and their impact on a substantial change of political culture in local communities. This study used descriptive qualitative methods, and research sites in the District Banyumanik, Semarang Municipal. This study concludes that changes in national politics at the procedural level after the 1998 reform do not substantially affect the change of political culture in local communities.